NEW REPORT OF LEAF SPOT DISEASE OF CLERODENDRUM INDICUM CAUSED BY CURVULARIA LUNATA - ANINDITA MUKHERJEE; ABHIJIT BANDHYOPADHYAY; SIKHA DUTTA (International Journal of Pharma and Bio Sciences, 2013)
This is a maiden report of necrotic leaf spot disease of Clerodendrum indicum, an important medicinal plant, caused by fungal pathogen Curvularia lunata. Clerodendrum indicum (L.) Kuntze, as an important medicinal plant is grown extensively in India, Nepal, China, Japan, Srilanka, West Indies etc. and considered for its potency against asthma, cough, fever, intestinal worms, arthritis etc. The fungal pathogen was isolated from the diseased plant tissue and pure culture was being established. It has been identified as Curvularia lunata The plant is native in India and is found throughout south eastern Asia. This plant is used to treat cough, asthma, bronchitis and other respiratory diseases. Morphological study, pathogenicity test , and 18s rDNA sequencing confirmed the pathogen Curvularia lunata.